The Strategic Policy of Child Marriage Prevention on Gender-Integrated (Strengthening Best Practice Areas Toward Child Marriage-Free Zones) - Trianah Sofiani (MUWAZAH : jurnal kajian gender, 2022)
This study analyzed the strategic policies for preventing early marriage in Rembang Regency. This evaluative study used interviews, questionnaires, and document studies methods for data collection. The result of the study showed that the gender-integrated early marriage prevention policy in Rembang district can be seen in regulations, budgets, the strengthening of child groups, institutions, and cooperation. Sufficient budget and human resources and the openness of information systems, were the strengths of the policy on preventing early marriage in this area. Otherwise, the partial activities, lacked of monitoring and evaluation, a commitment to gender mainstreaming was not yet optimal, a gender-biased organizational culture, the politics of budget that often changed, and the children's forum less active were the weaknesses in this policy. The national and international policies; discipline by the population administration; gender and child disaggregated data; the technology of information; collaboration with NGO and the private sector were the opportunities that must be considered for the success of this policy. On the other hand, we must watchful to policy threats, such as: lack of education, high poverty level, patriarchy, early marriage traditions, “ngemblok” tradition, the technology of information, the age limit for marriage has changed, the community involvement was very minimal, unbalanced of gender insight, and lack of understanding on children’s rights. The early marriage prevention policy has impacted the target groups, non-target groups, and direct and indirect costs. Optimization of early marriage prevention policies should be done by using Scheme 1, maximizing strengths to minimize the threats; Scheme 2, optimizing gender equality in regional apparatus organizations; and Scheme 3, monitoring and evaluation periodically and structurally. These schemes must pay attention to the five "rights". These five righst were choose the right policy and program, the right implementation, the right target, the right environment, and the last was the right process.